Health literacy as a determinant of HIV/AIDS preventive behavior: A cross-sectional study among university students in Yogyakarta, Indonesia - Latifahanun, Este; Aulia Rahmi, Safirina; Febriandi, Sarif; Ratih Resti Andani, Mahardika; Shinta P, Riadinata (Universitas Islam Negeri Alauddin Makassar, 2025)
Previous studies have shown a general association between health literacy and HIV/AIDS prevention behaviors; however, few have focused specifically on university students in educational hubs such as Yogyakarta, Indonesia. Moreover, the role of digital access and socio-cultural context in shaping student health literacy remains underexplored. This study aimed to analyze the relationship between health literacy levels and HIV/AIDS prevention behavior among university students in Yogyakarta. A cross-sectional analytical design was used involving 133 students recruited through consecutive sampling between May 5–23, 2025. Data were collected via a structured online questionnaire measuring both health literacy and HIV/AIDS prevention behavior. Bivariate analysis was conducted using the Chi-Square test. The findings revealed a statistically significant association between health literacy and HIV/AIDS prevention behavior (p = 0.000). Students with higher health literacy were substantially more likely to engage in preventive behaviors, including safe sex practices and HIV testing, than those with low health literacy. This study reinforces the critical role of health literacy in influencing HIV/AIDS prevention among university students. The findings support the integration of health literacy education into academic programs as a public health strategy. Health professionals and policymakers should prioritize targeted literacy interventions to enhance health behaviors among youth populations.